Thasmim Mawad Maharah al-Kalam Fi Istimdadiha Min al-Ayat al-Istifhamiyah Fi Surah al-An’am wa al-Mulk Li Thulab al-Ma’had al-‘Aly Ulum al-Qur’an Amuntai - Mubarak, Faisal; Sattar, Abdul; Arief, Ahmad Fahmy (Arabiyatuna: Jurnal Bahasa Arab, 2020)
The background of this research is based on the place where the research is conducted based on the needs of the High School Science of the Qur'an (STIQ) Amuntai on teaching materials and to develop Arabic learning material using Istifham verses, and also to test the truth of the design of teaching material compiled by researchers. The formulation of the problem of this research is as follows: how is the design of the speaking skill learning material by using Istifham verses in the Surah al-An'am and al-Mulk for Amuntai High School Science of the Qur'an (STIQ), while the purpose of this study is to know how to design learning materials speaking skill by using Istifham verses in surah Al An'am And Al Mulk for students of the Amuntai Qur'anic High School (STIQ).The research method is the Reseach & Development (R&D) method with a Quantitative approach and Qualitative. While the data collection tools used: Observations,Â  interviews,Â  Questionnaire, Test trials. The design model in the design preparation uses the Borg & Gall model using 5 design steps: Requirement Analysis, Product design, Trial/ product evaluation, Product revision, Product trial test. The results of the study both from the trial and questionnaire results are as follows: Istifham verses used in the design of teaching materials for the material of speaking skill in surah al-An'am and al-Mulk namely are contained adawat Istifham: Ø§Ù„Ù‡Ù…Ø²Ø© (Ø¡), Ù‡ÙŽÙ„Ù’, Ù…ÙŽØ§, Ù…ÙŽÙ†Ù’, Ù…ÙŽØªÙŽÙ‰, ÙƒÙŽÙŠÙ’ÙÙŽ, Ø£ÙŽÙŠÙ’Ù†ÙŽ, ÙƒÙŽÙ…Ù’, Ø£ÙŽÙŠÙÙ‘, Ø£ÙŽÙ†ÙŽÙ‘Ù‰. (2) The results of responses and assessments by material design experts in terms of the content of the material indicate the level of "very good" is â€œ90 %â€, and from the lecturer/ teacher the teacher shows the level of "very good" is â€œ82,5%â€, while the students show the response of the level of assessment of "sufficient" is â€œ50,86 %â€, While the effectiveness of the use of maharah kalam learning material design by using Istifham verses in the Surah Al An'am and Al Mulk for Amuntai Qur'an College (STIQ) students obtain significant results or are worthy of use.